Born too soon in a resource-limited setting: A 10-year mixed methods review of a special care baby unit for refugees and migrants on the Myanmar-Thailand border - Hashmi, Ahmar; Darakamon, Mu Chae; Aung, Ko Ko; Mu, Mu; Misa, Prapatsorn; Jittamala, Podjanee; Chu, Cindy; Phyo, Aung Pyae; Turner, Claudia; Nosten, Francois; McGready, Rose; Carrara, Verena I. (Frontiers in Public Health, 2023)
Background: Preterm birth is a major public health concern with the largest burden of morbidity and mortality falling within low- and middle-income countries (LMIC). Materials and Methods: This sequential explanatory mixed methods study was conducted in special care baby units (SCBUs) serving migrants and refugees along the Myanmar-Thailand border. It included a retrospective medical records review, qualitative interviews with mothers receiving care within SCBUs, and focus group discussions with health workers. Changes in neonatal mortality and four clinical outcomes were described. A mix of ethnographic phenomenology and implementation frameworks focused on cultural aspects, the lived experience of participants, and implementation outcomes related to SCBU care. Results: From 2008-2017, mortality was reduced by 68% and 53% in very (EGA 28-32 weeks) and moderate (EGA 33-36 weeks) preterm neonates. Median SCBU stay was longer in very preterm neonates compared to moderate: 35 (IQR 22, 48 days) vs. 10 days (IQR 5, 16). Care was longer: nasogastric feeding lasted 82% (IQR 74, 89) vs 61% (IQR 40, 76) of the stay, and oxygen therapy was used a median of 14 (IQR 7, 27) vs 2 (IQR 1, 6) days respectively. Nine interviews were conducted with mothers currently receiving care in the SCBU and four group discussions with a total of 27 local SCBU staff. Analysis corroborated quantitative analysis of newborn care services in this setting and incorporated pertinent implementation constructs including coverage, acceptability, appropriateness, feasibility, and fidelity. Coverage, acceptability, and appropriateness were often overlapping outcomes of interest, financial issues prior to or while admitted to the SCBU, and social issues and support systems as they adversely impacted SCBU stays. Interview and FGD findings highlight the barriers in this resource-limited setting as they impact the feasibility and fidelity of providing evidence-based SCBU care that often required adaptation to fit the financial and environmental constraints imposed by this setting. Discussion: This study provides an in-depth look at the nature of providing preterm neonatal interventions in a SCBU for a vulnerable population in a resource-constrained setting. These findings support implementation of basic evidence-based interventions for preterm and newborn care globally, particularly in LMICs.